Analisis kesulitan keterampilan berbicara siswa kelas I Sekolah Dasar dalam materi mengenali empat kata ajaib pada mata pelajaran Bahasa Indonesia - Rindy Antyka; Komala; Sofyan Nur Mahardhika (COLLASE (Creative of Learning Students Elementary Education), 2026)
This research is based on the difficulty of speaking elementary school grade I students on the magic four-word material. The purpose of this study is to identify learning difficulties on the speaking ability of elementary school students in the four-word magic material in the Indonesian language subject. This research method uses a qualitative approach with literature study. The subjects in this study are grade I students in one of the elementary schools in West Bandung Regency which amounted to 30 students. Based on the results of the study, grade I elementary school students in one of the elementary schools in West Bandung Regency experienced difficulties in learning the ability to speak on the material, recognizing four magic words which include; (1) difficulties in understanding the material, recognizing the four magic words; (2) Lack of mastery in using vocabulary; (3) Lack of Cooperation in the Group; and (4) Difficulty in Concentrating on Learning.